2006
DOI: 10.1016/s0022-5347(05)00334-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma With Nodal Metastases in the Absence of Distant Metastatic Disease (Clinical Stage TxN1-2M0): The Impact of Aggressive Surgical Resection on Patient Outcome

Abstract: Nodal metastasis with renal cell carcinoma is an independent predictor of prognosis in patients with M0 disease. Even in the absence of distant metastatic disease patients with positive nodes should be targeted for aggressive surgical resection, followed by clinical trials of adjuvant therapy to improve the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
43
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 19 publications
9
43
1
1
Order By: Relevance
“…11,17,19,20 Of the patients with metastatic disease, historically 40% have distant metastases only without evidence of LN involvement, 50% have both distant metastases and LN involvement, and up to 10% present with LN metastases. [21][22][23] Interestingly, in our series, patients with distant metastases also had a high rate of renal sinus and/or vein involvement: 68%, 92%, and 79% in groups Nx, N0, and N1, respectively. This suggests that renal sinus/vein involvement may be associated with alternative metastatic routes.…”
Section: Commentsupporting
confidence: 44%
“…11,17,19,20 Of the patients with metastatic disease, historically 40% have distant metastases only without evidence of LN involvement, 50% have both distant metastases and LN involvement, and up to 10% present with LN metastases. [21][22][23] Interestingly, in our series, patients with distant metastases also had a high rate of renal sinus and/or vein involvement: 68%, 92%, and 79% in groups Nx, N0, and N1, respectively. This suggests that renal sinus/vein involvement may be associated with alternative metastatic routes.…”
Section: Commentsupporting
confidence: 44%
“…The reported survival rate of patients with exclusive NM demonstrates great variability, and ranges from 5 to 40%. [3][4][5][6][7][8][9] Even after consideration of staging biases, these survival rates are in clear contrast with survival estimates from patients with localized disease (T 1-3 N 0 M 0 ), where 5-year survival exceeds 85%. Therefore, patients with NM have clearly more aggressive disease than even the worst variant of localized disease.…”
mentioning
confidence: 92%
“…This possibly justifies more aggressive treatment in patients with NM, such as nephrectomy and resection of the NM or nephrectomy followed by immediate systemic therapy. 3,9 Better ability to identify patients with NM can be useful in pre-operative counselling, targeting patients for potential involvement in adjuvant therapy trials, and may also assist in surgical planning if more extensive or complete nodal dissections are contemplated. 3,9 In this manuscript we address the issue of accurate identification of patients at risk of NM and we develop a multivariable (MVA) logistic regression model-based nomogram for this purpose.…”
mentioning
confidence: 99%
“…3 Of these patients with metastatic disease, historically 40% have distant metastases only without evidence of lymph node involvement, 50% have both distant metastases and lymph node involvement, and about 3% to 10% present with lymph node involvement only. [4][5][6][7] When lymph node dissection is performed, a number of studies have shown that positive lymph nodes have an independent adverse effect on outcome, irrespective of other variables. [8][9][10] Patients with node-positive disease have 5-year survival rates ranging from 5% to 35%.…”
Section: Discussionmentioning
confidence: 99%